2019
DOI: 10.1089/photob.2018.4512
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Home-Use Photobiomodulation Devices: A Systematic Literature Review

Abstract: Objective: Perform systematic literature review on photobiomodulation (PBM) devices used at home for nonesthetic applications. Background: Home-use PBM devices have been marketed for cosmetic and therapeutic purposes. This is the first systematic literature review for nonesthetic applications. Methods: A systematic literature search was conducted for PBM devices self-applied at home at least thrice a week. Two independent reviewers screened the articles and extracted the data. Treatment dosage appropriateness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Although the efficacy and safety of many home-use LED devices have been examined in a wide range of applications, including anti-aging and reduction in facial wrinkles, most studies reported positive results without any adverse events [5,17]. Nevertheless, a recent case study reported retinal damage due to prolonged exposure to a blue light home-use LED face mask [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacy and safety of many home-use LED devices have been examined in a wide range of applications, including anti-aging and reduction in facial wrinkles, most studies reported positive results without any adverse events [5,17]. Nevertheless, a recent case study reported retinal damage due to prolonged exposure to a blue light home-use LED face mask [17].…”
Section: Discussionmentioning
confidence: 99%
“…In photobiomodulation, larger wavelengths are associated with greater penetration depths of the beam in the tissues, while the irradiance is essentially the energy emitted by the light beam per unit area . Growing evidence suggests that the effects of photobiomodulation particularly benefit neural stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Laser-PBMT Anti-inflammatory: attenuates cytokine storm at multiple levels and reduces the major inflammatory metabolites [189][190][191][192][193][194] Increases collagen and protein production, cell proliferation, normalized of impaired circulation, decreases edema and swelling, and improves quality and tensile strength of tissue [189][190][191][192][193][194] PBMT reduces pulmonary microvascular leakage, IL-1β, IL-6, and intracellular ROS. On this note, PBMT as a single or adjunct treatment modality can modulate the cytokine storm and ARDS via its anti-inflammatory action [196][197][198][199] Reduces inflammation and promotes lung healing 199,205,206 and minimizes the scarring process [189][190][191][192][193][194] Has an immunomodulator effect in improving immune functional and modulating the cellular and molecular activities of the cytokine storm of SARS-CoV-2 200,203,206 It is a safe, effective, low-cost modality without any side effects that may be combined with conventional treatment of ARDS [196][197][198][199] Minimizes the length of time needed on a ventilator, enhance the healing process, and shorten recovery time in COVID-19 patients 199,200 PBMT as a single or adjunct treatment modality can modulate the cytokine storm and ARDS via its anti-inflammatory action [196][197][198]…”
Section: Antiviral Drugsmentioning
confidence: 99%
“…187,188 It is welldocumented in the scientific literature that phototherapy presents a promising noninvasive treatment modality in tissue healing and regeneration, as well in pain management. [189][190][191][192][193][194] The Rationale for Use of PBMT (Laser and LEDs) in COVID-19…”
Section: Future Noninvasive Therapymentioning
confidence: 99%